International pre-service teachers’ anxiety and coping strategies: Perspectives of a geographically disadvantaged Islamic boarding school - ., Dzulfikri; Azami, Mochamad Imron (Englisia Journal, 2024)
This study aims to delve into anxiety experienced by international pre-service teachers who taught English in a very remote Islamic boarding school in Malaysia and how they cope with their feelings. This study employs narrative inquiry involving two research participants. The findings reveal that both participants felt anxious particularly because the students have very diverse English competencies which further creates negative effects such as unequal class participation, losing interest, etc. which subsequently affect classroom management. Varying teaching techniques and employing strategies favoured by the majority of students are considered to be the best ways to improve both their class participation and learning interest; hence, alleviating their anxiety. They include teaching through language games, learning through songs, grouping students in varied competence levels, and prized quizzes. Cultural differences are also the factors causing their anxiety, further calling for intercultural competence when living through cross-cultural encounters. Immersing in the target community is a strategic way to achieve such competence. This article ends with further pedagogical implications.